2010
DOI: 10.1007/s11671-010-9701-3
|View full text |Cite
|
Sign up to set email alerts
|

Periodically Aligned Si Nanopillar Arrays as Efficient Antireflection Layers for Solar Cell Applications

Abstract: Periodically aligned Si nanopillar (PASiNP) arrays were fabricated on Si substrate via a silver-catalyzed chemical etching process using the diameter-reduced polystyrene spheres as mask. The typical sub-wavelength structure of PASiNP arrays had excellent antireflection property with a low reflection loss of 2.84% for incident light within the wavelength range of 200–1,000 nm. The solar cell incorporated with the PASiNP arrays exhibited a power conversion efficiency (PCE) of ~9.24% with a short circuit current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 29 publications
1
40
0
2
Order By: Relevance
“…X. Li et al studied the efficient antireflective properties of periodically aligned Si nano-pillar arrays [14]. They fabricated the periodically nano-patterned Si structures by using silver catalyzed chemical etching process and found that the reflection can be remarkably reduced in the wavelength range of 200∼1000 nm.…”
Section: Resultsmentioning
confidence: 99%
“…X. Li et al studied the efficient antireflective properties of periodically aligned Si nano-pillar arrays [14]. They fabricated the periodically nano-patterned Si structures by using silver catalyzed chemical etching process and found that the reflection can be remarkably reduced in the wavelength range of 200∼1000 nm.…”
Section: Resultsmentioning
confidence: 99%
“…7 8 However, film based Sidevices do not have efficient photoresponse properties due to the layer reflectivity and longer carrier collection distance. 9 10 In order to overcome these obstacles, we need to introduce the different structure such as wires, cones/tips and pillars in the range of microns to nanoscales, [11][12][13][14][15][16] which enable to suppress the device reflectance to enhance the device efficiency. In addition, the smaller diameter of pillars or wires giving an optimum carrier collection distance for generated charge carries in depletion region under light illuminations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the smaller diameter of pillars or wires giving an optimum carrier collection distance for generated charge carries in depletion region under light illuminations. 11 13 Herein, we mainly focused on Si pillar arrays with a probability of having low defects and desirable widths. Moreover, by introducing the anti-reflective coating on Si pillar arrays lead to further reduction of device reflectivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, more than 35% of incident light is reflected back from silicon (Si) surfaces by Fresnel reflection because of the large refractive index discontinuity at the interface of Si and air. To suppress the Fresnel reflection, ARCs directly patterned on Si substrates have been extensively explored both experimentally [1][2][3][4] and theoretically, [5][6][7] and various randomly or periodically structured surfaces, including upright or inverted pyramids, 1,2,9,10 nanopillars, [11][12][13][14][15] nanowires/nanocones, 3,16,17 and porous structures 18 have been reported. However, the controllable, low-cost, and efficient fabrication of such nanostructures still remains a problem.…”
Section: Introductionmentioning
confidence: 99%